Southeast asian affairs 2010 / edited by Daljit Singh - Singh, Daljit (ed.) (Singapore, 2010)
Founded in 1974, Southeast Asian Affairs provides, without fear or favour, informed and in-depth annual analyses of this vibrant region and its component countries. It is the only publication which does this and is in its own class without peers. It is a mandatory reference and read for those seriously interested in knowing Southeast Asia. -Professor A.B. Shamsul, Founding Director, Institute of Ethnic Studies, Universiti Kebangsaan Malaysia. ""Now in its 37th edition, Southeast Asian Affairs offers an indispensable guide to this fascinating region. Lively, analytical, authoritative, and accessible, there is nothing comparable in quality or range to this series. It is a must read for academics, government officials, the business community, the media, and anybody with an interest in contemporary Southeast Asia. Drawing on its unparalleled network of researchers and commentators, ISEAS is to be congratulated for producing this major contribution to our understanding of this diverse and fast-changing region, to a consistently high standard and in a timely manner." -Hal Hill, H.W. Arndt Professor of Southeast Asian Economies, Australian National University.
Keywords: Southeast Asia-Periodicals